New and Old Samoyed Etymologies ... - Aikio, Ante (Société Finno-Ougrienne, 2002)
The paper discusses etymological equations between Samoyedic and Finno-Ugric languages. The presentation includes both new etymologies and comments on previously presented comparisons that have been ignored or rejected in the strictest treatments of Uralic historical phonology. A total of 28 Samoyedic word families are subjected to etymological analysis, and several other etymologies are briefly commented upon. It is argued that even in a framework of relatively strict sound laws, the number of Proto- Uralic etymologies with Samoyedic cognates turns out to be higher than the most critical estimates presented earlier. ...